2023
DOI: 10.26434/chemrxiv-2023-c1pk9
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Manufacturing Strategy Utilizing a Continuous Mode Reactor toward Homogeneous PEGylated Bioconjugate Production

Abstract: Protein PEGylation is a traditional bioconjugation technology that enhances the therapeutic efficacy and in vivo half-life of proteins by the formation of covalent bonds with polyethylene glycol (PEG). The most established methodology for PEGylation utilizes activated ester-incorporating PEG reagents; however, the high reactivity of these reagents induces a random reaction with lysine residues on the protein surface, resulting in a heterogeneous mixture of PEGylated proteins. Moreover, the traditional batch-mo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
(36 reference statements)
0
4
0
Order By: Relevance
“…These results were similar to those observed in previous FMR experiments. 15 The aggregation rates assessed by SEC showed that the PEGylation-induced aggregation was insignificant, not exceeding 1% (Figure 5a). 25 In this study, monopegylation was performed on a scale of several hundred milligrams, successfully producing 351 mg of mono-PEGylated IL-6.…”
Section: ■ Results and Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…These results were similar to those observed in previous FMR experiments. 15 The aggregation rates assessed by SEC showed that the PEGylation-induced aggregation was insignificant, not exceeding 1% (Figure 5a). 25 In this study, monopegylation was performed on a scale of several hundred milligrams, successfully producing 351 mg of mono-PEGylated IL-6.…”
Section: ■ Results and Discussionmentioning
confidence: 96%
“…36 Given the high solvent-accessible surface area and abundance of Lys in IL-6, selective PEGylation becomes a challenge compared with proteins such as lysozyme, which have a limited number of Lys residues. 15 Additionally, the tendency of IL-6 to aggregate complicates its handling. 23 We performed PEGylation on such a complex protein substrate to demonstrate the versatility and efficacy of the Portable FMR.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Recent studies have explored FMR technology for next-generation protein therapeutics, including antibody−drug conjugate production 12 and PEGylation processes. 13 Expanding upon these foundational studies, this study presents an advancement with the successful implementation of a cascaded-mixer system, enabling FMR-mode protein refolding. We studied the conformational changes of the cytokine interleukin (IL-)6 as a model, 18 at different pH and in various organic solvents 19,20 to determine the most effective way to generate the optimal IL-6 conformation.…”
Section: ■ Introductionmentioning
confidence: 99%